2001
DOI: 10.1002/ijc.1640
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL, Fasl and a blocking anti‐DR5 antibody augment paclitaxel‐induced apoptosis in human non‐small‐cell lung cancer

Abstract: Key words: lung cancer; paclitaxel; TRAIL; DR5; FasL; apoptosisLung cancer is among the most commonly occurring malignancies worldwide and accounts for 1,193,000 deaths in 1999. 1 In the United States, lung cancer is the leading cause of cancer death in men, and it is the second most frequent cancer in women after breast cancer. NSCLC accounts for about 75 to 80% of lung cancer cases and carries an overall 5-year survival of about 10 -15% despite recent advancements in multimodality therapies (chemoand radio-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In combination with chemotherapy, TRAIL is synergistic (89), and this effect does not correlate with either CASP8 nor FLIP expression level (90). Simultaneous expression of TRAIL and p53 increases apoptosis sensitivity in NSCLC cell lines (91).…”
Section: Casp8 Regulation In Non -Small Cell Lung Cancermentioning
confidence: 99%
“…In combination with chemotherapy, TRAIL is synergistic (89), and this effect does not correlate with either CASP8 nor FLIP expression level (90). Simultaneous expression of TRAIL and p53 increases apoptosis sensitivity in NSCLC cell lines (91).…”
Section: Casp8 Regulation In Non -Small Cell Lung Cancermentioning
confidence: 99%
“…TRAIL, also known as APO-2L [1,2] , is highly homologous to FasL. TRAIL is capable of inducing apoptosis of many kinds of cancer cells but nontoxic to normal cells [3][4][5][6][7][8][9][10][11][12][13] . It has been found that cells of different cancers and even different types of cells of a cancer exhibit significantly different sensitivity to TRAIL [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] Recently, studies have shown that both FasL and TRAIL can induce apoptosis in a number of tumor cell lines of various origins. [25][26][27][28][29] These proteins may have an advantage as therapeutics for brain tumors (BTs), since both they and their receptors are membrane proteins. Death ligand-induced apoptosis is mediated through cellcell contact, allowing the cell expressing the ligand to induce apoptosis in a number of surrounding receptorexpressing cells -a bystander effect not directly achieved with intracellular apoptosis-inducing proteins like p53 and Bax, and which does not require transport of prodrugs across the blood-brain barrier, as is the case for TK and cytosine deaminase.…”
mentioning
confidence: 99%